2011
DOI: 10.1097/sla.0b013e31823594ae
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up After Right Hepatectomy for Adult Living Donation and Attitudes Toward the Procedure

Abstract: ALDLT donors are at risk for long-term complaints that are neither reflected nor related to early complications. This information should be included in both the donor evaluation and the ALDLT decision-making process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 42 publications
7
52
0
3
Order By: Relevance
“…The subgroup analysis of the Istambul series [7] revealed a much higher overall complication rate in non-MHV (22.4%) vs MHV-contained remnants (7.8%) mirroring our own experience with the tendency for (-) MHV remnants to have more complications than (+) MHV ones (25% vs14%). Furthermore, our experience as well as that of others did not reveal any late complications attributable to remnant size or MHV-status [7,35] . Our virtual data however, showed that the "sacrifice" of the left sided MHV-4A/B drainage in remnants due to MHV inclusion with the graft was associated with large congestive volumes (CV-index of 36.9 ± 11.6 %RV) that resulted in a significant reduction of non-congestive volumes (non-congestive-RVBWR) safely drained by LHV.…”
Section: Table 4 Middle Hepatic Vein Management In Small-for-size -Rementioning
confidence: 71%
“…The subgroup analysis of the Istambul series [7] revealed a much higher overall complication rate in non-MHV (22.4%) vs MHV-contained remnants (7.8%) mirroring our own experience with the tendency for (-) MHV remnants to have more complications than (+) MHV ones (25% vs14%). Furthermore, our experience as well as that of others did not reveal any late complications attributable to remnant size or MHV-status [7,35] . Our virtual data however, showed that the "sacrifice" of the left sided MHV-4A/B drainage in remnants due to MHV inclusion with the graft was associated with large congestive volumes (CV-index of 36.9 ± 11.6 %RV) that resulted in a significant reduction of non-congestive volumes (non-congestive-RVBWR) safely drained by LHV.…”
Section: Table 4 Middle Hepatic Vein Management In Small-for-size -Rementioning
confidence: 71%
“…The duration of the follow-up has also been controversial. 18 It is obvious that limiting the observation to the hospital stay is insufficient due to major center variations, and a consensus seems to arise proposing a minimum of 3 months. [19][20][21][22][23][24][25][26][27] In the current study, a number of events occurred between the time of discharge and 3 months postoperatively, but very few afterward corroborating the standardized use of benchmarking at 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the partial liver's ability to regenerate both as a graft (in the recipient) and remnant (in the donor), probably is the main justification for the safety of right lobe living donor liver transplantation (RLLDLT). A review of previous studies showed that full recovery of the liver donor occurs soon after right lobe donation (1); yet, other studies that addressed the ethical and psychological aspects in living donation showed that even several months after RL donation, donors do not show full recovery to their preoperative status with respect to social, work, and health parameters (2,3). The same questions could thus be posed regarding the ad integrum recovery (recovery to predonation status) of the donors' liver function and volume.…”
Section: Recovery Of Normal Liver Function (Prothrombin Time [Pt]mentioning
confidence: 99%